2017
DOI: 10.1073/pnas.1706593114
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial interaction network of abscisic acid receptors and coreceptors from Arabidopsis thaliana

Abstract: The phytohormone abscisic acid (ABA) is induced in response to abiotic stress to mediate plant acclimation to environmental challenge. Key players of the ABA-signaling pathway are the ABA-binding receptors (RCAR/PYR1/PYL), which, together with a plant-specific subclade of protein phosphatase 2C (PP2C), form functional holoreceptors. The Arabidopsis genome encodes nine PP2C coreceptors and 14 different RCARs, which can be divided into three subfamilies. The presence of these gene families in higher plants point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
133
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 52 publications
6
133
0
Order By: Relevance
“…Currently, at least six Arabidopsis PP2Cs, namely ABI1, ABI2, PP2CA/AHG3, AHG1, HAB1 and HAB2, are known to negatively regulate ABA signaling as well as Highly ABA-Induced 1-3 (HAI1-HAI3) phosphatases, although HAI1-3 have less impact in ABA sensitivity and more in order to regulate particular drought resistance traits Bhaskara et al, 2012;Tischer et al, 2017). PP2CA is a negative regulator of ABA signaling both in seed and vegetative ABA responses, and RGLG1/5 and other E3 ligases regulate PP2CA half-life (Sheen, 1998;Kuhn et al, 2006;Yoshida et al, 2006;Lee et al, 2009;Rubio et al, 2009;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, at least six Arabidopsis PP2Cs, namely ABI1, ABI2, PP2CA/AHG3, AHG1, HAB1 and HAB2, are known to negatively regulate ABA signaling as well as Highly ABA-Induced 1-3 (HAI1-HAI3) phosphatases, although HAI1-3 have less impact in ABA sensitivity and more in order to regulate particular drought resistance traits Bhaskara et al, 2012;Tischer et al, 2017). PP2CA is a negative regulator of ABA signaling both in seed and vegetative ABA responses, and RGLG1/5 and other E3 ligases regulate PP2CA half-life (Sheen, 1998;Kuhn et al, 2006;Yoshida et al, 2006;Lee et al, 2009;Rubio et al, 2009;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…From these data a picture of the drought signaling system emerges that is differently tuned in the resistant species relative to Ath . Intriguingly, several of the genes that are constitutively expressed at higher levels in the resistant species were shown in Ath to increase WUE and drought resistance (Tischer et al ., ). This opens the possibility that other signaling genes expressed at higher levels in Aly and Esa may have similar beneficial effects.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that a smaller stomata aperture affects the water use efficiency (WUE) of the resistant Aly and Esa . Importantly, a recent overexpression screen found that higher levels of the Aly ‐ and Esa ‐elevated ABA receptors increase Ath WUE (Yang et al ., ; Tischer et al ., ), suggesting a causal contribution to Aly and Esa drought resistance. While the functional orthology of the Aly and Esa proteins remains to be shown, this possibly convergent evolution of higher ABA receptor levels in Aly and Esa is consistent with their resistant phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we used poplar lines overexpressing the ABA receptor RCAR1/PYL9 . Poplar RCAR1/PYL9 is induced by ABA and interacts with HAIs (highly ABA-induced, which are members of the PP2C-A clade), demonstrating widely conserved functions in both Arabidopsis and poplar Tischer et al, 2017). Yu et al (2017a,b) observed higher biomass production in RCAR1 overexpressing poplar lines and ascribed this behaviour to hypersensitive stomatal regulation and activation of oxidative stress responses.…”
Section: Drought Stress Uncovers Novel Functions For Aba-related Genementioning
confidence: 99%